2021
DOI: 10.3390/met11091373
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Capturing Twin Nucleation in Crystal Plasticity for Hexagonal Metals

Abstract: Owing to its ability to incorporate Schmid’s law at each integration point, crystal plasticity has proven a powerful tool to simulate and predict the slip behavior at the grain level and the ensuing heterogeneous stress/strain localization and texture evolution at the macroscopic level. Unfortunately, notwithstanding substantial efforts during the last three decades, this remarkable capability has not been replicated for materials where twinning becomes a noticeable deformation mechanism, namely in the case of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 224 publications
0
4
0
Order By: Relevance
“…It uncovers that twinning is not completely absent within ultrafine grains, but rather occurs under extremely stringent conditions. Numerous studies have demonstrated that dislocations play a pivotal role in the initiation of twinning in pure Ti [37][38][39]. Furthermore, the Hall-Petch relationship, which is based on the principle of dislocation obstacle at grain boundaries, has effectively explained the origin of strength [15].…”
Section: Resultsmentioning
confidence: 99%
“…It uncovers that twinning is not completely absent within ultrafine grains, but rather occurs under extremely stringent conditions. Numerous studies have demonstrated that dislocations play a pivotal role in the initiation of twinning in pure Ti [37][38][39]. Furthermore, the Hall-Petch relationship, which is based on the principle of dislocation obstacle at grain boundaries, has effectively explained the origin of strength [15].…”
Section: Resultsmentioning
confidence: 99%
“…Elastic part includes the information about rotation and stretching, plastic part influences on plastic shearing on crystallographic slip systems and defines dislocations (Fig. 1) (Paudel et al, 2021). 2) The macroscopic velocity gradient 𝑳 is decomposed additively into elastic and plastic parts (Eq.…”
Section: Constitutive Equations Of Crystal Plasticity Theorymentioning
confidence: 99%
“…[ 203 ] This, nevertheless, cannot capture the nucleation of a twin as a geometric object in a mechanically loaded crystal. However, the general mechanism of twin nucleation has been extensively studied within the frameworks of crystallographic theory and crystal plasticity theory over the last few decades, [ 202,204–210 ] including twins in low‐symmetry systems. [ 211 ] Hence, crystallography‐based models could be related to experimental observations and ab initio approaches, with the aim of qualitatively explaining the difference between Type I and Type II nucleation.…”
Section: Interaction With External Forces: Elastic Constants and Mobi...mentioning
confidence: 99%